(untitled) ("Temas Sociais" Journal, 2024)
The profound changes in society have promoted shifts in housing policies linked to the sociocultural transformations of individuals’ lives, increasingly challenging Social Services to adopt a critical, structuralist, and mediation-oriented practice in facilitating access. The new generation of housing policies offers innovative tools in an attempt to alleviate the structural problem of housing rights conditioning in Portugal. Currently, policies have alternated between the direct promotion of housing (such as construction in situations of housing shortage among insolvent social strata) and indirect promotion (through the provision of financial assistance and tax benefits as well as support for home ownership) (Matos, 2001; Serra, 2002; Antunes, 2018). In the scope of this article, we were interested in the perspective of Social Workers on how the real possibilities of access are perceived within the framework of new policies and potential transformations in the field of practices. How do professionals perceive the changes in housing policy? What are the theories of practice? How does it articulate with universalist resources/policies capable of reinforcing the right to housing? Methodologically, we organized the research as case studies, mobilizing qualitative methods to study practices and access views in 4 municipalities in the northern region of Portugal. The research revealed positive views of policy transformation, notably due to the leveraging of new resources that increase access. Professionals reproduce an approach close to classical, individualistic-reformist views, of an assistance-oriented type, heavily supported by municipal regulations. It is understood that the scarcity of resources has triggered a normative and technocratic professionalism, at the expense of reflective and critical stances, of political mediation. The narrative of effectiveness and efficiency does not always correspond to empirical evidence. It is important for social workers to adopt an alternative paradigm of practices that emphasizes mediation, given that the housing problem is a structural issue.